Improving the Effectiveness of Disaster Mitigation in Wonogiri Regency, Indonesia Using House of Risk Method - Setiawan, Eko; Pramana, Gufron Adhi (Indonesian Journal of Geography, 2023)
Wonogiri Regency, the Republic of Indonesia, is an area that has potential to be affected by various types of disasters. This study aims to identify the types of disaster potentials in the Wonogiri Regency and to provide recommendations for effective disaster mitigation strategies that can be effectively implemented by the Regional Disaster Management Agency (Badan Penanggulangan Bencana Daerah or BPBD in short) of the Wonogiri Regency during 2021-2026 time period by using the House of Risk (HoR) method. The study found that floods, landslides, strong winds, volcanic eruptions, earthquakes, tsunamis, forest and land fires, droughts, and extraordinary events are likely to take place in the regency. The implementation of the HoR phase 1 yields 19 disaster risk events and 19 disaster risk agents. The use of Pareto diagram to the disaster risk agents results in 8 dominant risk agents of disaster, namely “Unstable ground”; “The trees are too old and fragile”; “The trees are too dense”; Lack of water resources”; Heavy rain intensity”; “Struck by disaster materials”; “Epidemic of a disease”; and “The building construction is not strong”. The implementation of the HoR phase 2 produces 15 mitigation strategies along with their priority order in which the 5 mitigation strategies with the highest priority are “Working with related parties to reduce the potential of disasters”; “Conducting socialization and education of disasters”; “Establishing disaster-resilient villages”; “Mapping disaster-prone areas”; and “Training for disaster volunteers”.